Demystifying Sovereign ESG - Gratcheva, Ekaterina M. (World Bank, Washington, DC, 2021)
The evolution of sustainable finance to mainstream finance has been motivated by a growing demand for the financial sector to play a greater role in the transformation of the current economic model into a more sustainable one. The introduction of the United Nation’s (UN) Sustainable Development Goals and the Paris Agreement on climate change in 2015 have helped galvanize a societal shift to ensure a sustainable future and to fight climate change in particular. As a result, the pace of environmental, social, and governance (ESG) integration, which has become the most prevalent form of sustainable finance, has accelerated in recent years. Market participants continue to grapple with adapting the ESG framework to the sovereign context, despite significant progress of ESG integration in the corporate bond and equity asset class. This challenge is due to the multifaceted nature of ESG-related issues facing governments in relation to corporate entities, as well as a more complex transmission mechanism of the sovereign debt asset class to sustainable outcomes in the real economy. This paper demystifies sovereign ESG as a distinct segment of the ESG sector by assessing the major sovereign ESG providers that have laid the foundation for the operationalization of ESG investing in sovereign fixed income markets.